Hysteresis SVM for Coupled Inductor Z Source Diode Clamped 3-level Inverter based Grid Connected PV System - R. Palanisamy; A.U Mutawakkil; K. Vijayakumar (Institute of Advanced Engineering and Science, 2016)
Due to its advantages such as it can defeat problems such as leakage current and insertion of DC in the grid and provides low stress on power devices, Diode clamped three-level inverter (DCTLI) is habitually used in transformerless photovoltaic (PV) connected to grid network. But it still has a problem of shoot-through which dwells in its legs, so its operation not reliable. Z source network is employed to permit operation without shoot through risk and improve its reliability. Coupled inductors are replace line transformers in to attain lower cost, reduced size, and improved its reliability and efficiency. Coupled inductor which avoids leakage current problem and losses. It employs coupled inductor z source diode clamped three level inverter (CI-Z-DC-TLI) to boost the voltage and further improve the reliability of the system by preventing the shoot through the problem. The proposed system assures that common-mode voltage and shoot-through risk is avoided. Moreover, controlling DC-TLI with Hysteresis SVM algorithm which improves output voltage and current control. Simulation and experimental results of this proposed system were analyzed using MATLAB environment and FPGA hardware.